Mental health of prisoners: prevalence, adverse outcomes, and interventions - Fazel, S; Hayes, A; Bartellas, K; Clerici, M; Trestman, R (Elsevier, 2016)
More than 10 million people are imprisoned worldwide, and the prevalence of all investigated mental disorders is higher in prisoners than in the general population. Although the extent to which prison increases the incidence of mental disorders is uncertain, considerable evidence suggests low rates of identification and treatment of psychiatric disorders. Prisoners are also at increased risk of all-cause mortality, suicide, self-harm, violence, and victimisation, and research has outlined some modifiable risk factors. Few high quality treatment trials have been done on psychiatric disorders in prisoners. Despite this lack of evidence, trial data have shown that opiate substitution treatments reduce substance misuse relapse and possibly reoffending. The mental health needs of women and older adults in prison are distinct, and national policies should be developed to meet these. In this Review, we present clinical, research, and policy recommendations to improve mental health care in prisons. National attempts to meet these recommendations should be annually surveyed.